Peningkatan Kesadaran Melestarikan Lingkungan Hidup Berbasis Humanisme Pendidikan Agama - Karim, Abdul (Humanist Journal, 2023)
Increased environmental degradation of the forest and the lack of clarity of the solution are interesting to examine. This study aims to get answers to the process of raising public awareness to preserve the environment. This research uses Participation Action Research approach. The results of the research show that the conservation awareness development process is done by developing participation through group activities as communication media to formulate the cause of environmental damage, and to find problem solving through religious education. Internal problems in developing environmental conservation awareness are economic background, low understanding of the impact on the environment, and low understanding of religion. External factors include provocation from outside the area that affect the community to do forest destruction, high selling value, and the availability of markets that take advantage of theft. The solution to develop public awareness is to improve the attitude of humanism through the socialization of environmental conservation materials and religious education with an integrated approach.